Cores da docência: o cinema como sol de uma formação instituinte no ensino público - Silva, Roberto Silva da (2021)
This master’s thesis is the result of a survey carried out with public school educators who use filmmaking as a device in their pedagogical practice. The role of this teacher in the construction of the teaching of these teachers is the subject of the research. The question that is constantly around is: how did filmmaking act in the construction of the teaching of film-producing teachers at school? This study seeks to understand how the experiences of educators with the seventh art affect their practices with students. How aesthetic experiences with cinema acted in the construction of these subjects' teaching, providing an opportunity to see how we can understand it. The autobiographical research was inspired by the Pedagogy of Observance (Celorio, 2015) and consisted of three interviews with teachers from Recife (PE), Palmeira dos Índios (AL) and Campo Bom (RS). These resulted in three cinematographic sinopsis that allowed the understanding of the crossing of cinema in the teaching of the research subjects. This understanding was based on the Bantu-Kongo cosmogram translated from Bakongo orality by Bunseki Fu-kiau (Santos, 2019). The communication between the north and south cosmovisions was possible because at all ontological stages there is a solar relationship between what Castoriadis (1982) established as representations of the instituted imaginary of the community field with the radical imaginary, of the subjective domain (ubuntu) . Such a process is solar because an exterior phenomenon acts metaphysically similar to the Sun by activating particles in the physical domain. There is a solar moment (kibanji) that radiates a magma, the meeting of imaginary representations. As it changes stages - black, red, white and yellow - it constitutes a fundamental instituting imaginary of cinematographic pedagogical practices. The notes in this script lead to professionality as opposed to the idea of professionalism, teaching, that is, a more organic relationship with the device that affects the being (muntu) in a deeper, intangible way (mpemba). That's why, even marginalized by the institutional, the cinema device starts to occupy a symbolic place in the practice of these educators.